The Role of E-commerce for MSMEs as a Digital Marketing Strategy in Facing Industrial Revolution 4.0 - Sugiharto, Bagus Hari (Management Studies and Business Journal (PRODUCTIVITY), 2024)
In the era of industrial revolution 4.0, the role of E-commerce for Micro, Small and Medium Enterprises (MSMEs) is becoming increasingly important as a digital marketing strategy. This research aims to investigate the impact of E-commerce adoption by MSMEs in facing changes in global business dynamics. Through the Systematic Literature Review method, we analyzed relevant academic literature to understand the level of adoption, benefits, digital marketing strategies, and the impact of the industrial revolution 4.0 on MSMEs that adopt E-commerce. The research results show that MSMEs that adopt E-commerce experience increased competitiveness through market expansion, increased operational efficiency, and direct interaction with consumers. Digital marketing strategies, such as the use of social media and online advertising, dominate MSME efforts to increase visibility. The role of E-commerce has also proven vital in helping MSMEs adapt to the industrial revolution 4.0. The conclusions of this research highlight the complexity of the challenges and opportunities facing MSMEs, including technological barriers and the need for digital skills development. Policy implications include government support, digital skills development, facilitation of collaboration between MSMEs, and industry 4.0 awareness campaigns. This research provides in-depth insight into the crucial role of E-commerce for MSMEs in facing the industrial revolution 4.0, with the hope of providing guidance for practitioners, researchers and policies to support the growth and sustainability of MSMEs in this digital era.